THE INFLUENCE OF SITUATIONAL LEADERSHIP STYLE, TRAINING AND WORKLOAD ON EMPLOYEE PERFORMANCE AT THE J&T XPRESS EXPEDITION COMPANY BLANGKEJEREN BRANCH, GAYO LUES - Sandra Abadi; Ibrahim Qamarius; Nurfaliza; Yanita (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research aims to determine the influence of situational leadership style, training, and workload on employee performance at J&T Xpress Blangkejeren Branch, an expedition company in the field of shipping goods in Gayo Lues. By using SPSS version 29, the research results found that situational leadership style had a significant effect on employee performance, and training had a significant positive effect on employee performance. This study also found that workload has a significant impact on employee performance. The research results show that leadership style, training and workload are factors that influence employee performance at J&T Express Blangkejeren Branch.